2014
DOI: 10.1039/c3cc48466a
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical hydrates under ambient conditions from high-pressure seeds: a case study of GABA monohydrate

Abstract: The monohydrate form of the neurotransmitter γ-amino butyric acid (GABA) has been crystallised in the 0.4-0.8 GPa pressure range, recovered to ambient pressure and then used as a seed. Theoretical calculations indicate that this hydrate is only thermodynamically favoured over the two anhydrous forms at high pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 38 publications
1
58
0
1
Order By: Relevance
“…Increased thermodynamic stability with increasing pressure could however arise in binary systems from differential enthalpies of solvation. This seems to be the case for GABA monohydrate 38 where periodic DFT calculations at 0 K showed that at high pressure the enthalpy of hydration becomes increasingly more negative. GABA monohydrate can be recovered under ambient-pressure conditions, and used for seeding, because under these conditions it is energetically close to the anhydrous polymorph plus ice.…”
Section: Discussionmentioning
confidence: 97%
“…Increased thermodynamic stability with increasing pressure could however arise in binary systems from differential enthalpies of solvation. This seems to be the case for GABA monohydrate 38 where periodic DFT calculations at 0 K showed that at high pressure the enthalpy of hydration becomes increasingly more negative. GABA monohydrate can be recovered under ambient-pressure conditions, and used for seeding, because under these conditions it is energetically close to the anhydrous polymorph plus ice.…”
Section: Discussionmentioning
confidence: 97%
“…It complies with the pressure-promoted solvation observed in MOFs and molecular crystals. [27][28][29][30] It allows more compact packing of the molecules in the limited space, enabling the formation of solvates with possible technological applications. 31 The molecular volume of the g-CD-MOF-1 phase a crystal at 0.16 GPa is higher than that at ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
“…There are many types of crystallographic studies that cannot afford excluding the required data points from refinement because the entire dataset is too small. Such studies include low-resolution macromolecular studies, highpressure studies, neutron studies, and some of the latest data from free electron lasers (21,22,30).…”
Section: Discussionmentioning
confidence: 99%
“…In high-pressure crystallography the situation is even worse because the incompleteness of the data owing to shadows from the experimental setup is systematic and leads to data-to-parameter ratios too low to rely on R1 alone. The entire dataset may have fewer than 500 observations (22).…”
Section: Significancementioning
confidence: 99%